Adult offspring of high-fat diet-fed dams can have normal glucose tolerance and body composition - Platt, K. M. (Cambridge University Press, 2014)
Maternal high-fat diet consumption and obesity have been shown to program long-term obesity and lead to impaired glucose tolerance in offspring. Many rodent studies, however, use non-purified, cereal-based diets as the control for purified high-fat diets. In this study, primiparous ICR mice were fed purified control diet (10–11 kcal% from fat of lard or butter origin) and lard (45 or 60 kcal% fat) or butter (32 or 60 kcal% fat)-based high-fat diets for 4 weeks before mating, throughout pregnancy, and for 2 weeks of nursing. Before mating, female mice fed the 32 and 60% butter-based high-fat diets exhibited impaired glucose tolerance but those females fed the lard-based diets showed normal glucose disposal following a glucose challenge. High-fat diet consumption by female mice of all groups decreased lean to fat mass ratios during the 4th week of diet treatment compared with those mice consuming the 10–11% fat diets. All females were bred to male mice and pregnancy and offspring outcomes were monitored. The body weight of pups born to 45% lard-fed dams was significantly increased before weaning, but only female offspring born to 32% butter-fed dams exhibited long-term body weight increases. Offspring glucose tolerance and body composition were measured for at least 1 year. Minimal, if any, differences were observed in the offspring parameters. These results suggest that many variables should be considered when designing future high-fat diet feeding and maternal obesity studies in mice.